2014
DOI: 10.1039/c4ra09184a
|View full text |Cite
|
Sign up to set email alerts
|

A study using quantum chemical theory methods on the intrinsic fluorescence emission and the possible emission mechanisms of PAMAM

Abstract: In recent decades, it has been found and determined that poly-amidoamine (PAMAM) can give fluorescence emission under certain conditions. PAMAMs possess amide, primary amine and tertiary amine groups, which are not typical fluorescence emission groups. The fluorescence emission centers and mechanisms of PAMAM were studied. In this report we used quantum chemical TDDFT methods to calculate the absorption and emission states of the chemical components of PAMAM, which including amide, amide resonance structure im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Except for the mentioned work of Larson and Tucker, that measured fluorescence lifetimes on anionic PAMAM dendrimer [5] . The others research groups working with PAMAM DG4.0, proposed as fluorophores the inner tertiary amines and the tautomeric amido‐imide balance [9b,c] . In those works, a theoretical calculation of the structures responsible for the emission of fluorescence is carried out, concluding that the deprotonated tertiary amines (basic pH) do not emit fluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the mentioned work of Larson and Tucker, that measured fluorescence lifetimes on anionic PAMAM dendrimer [5] . The others research groups working with PAMAM DG4.0, proposed as fluorophores the inner tertiary amines and the tautomeric amido‐imide balance [9b,c] . In those works, a theoretical calculation of the structures responsible for the emission of fluorescence is carried out, concluding that the deprotonated tertiary amines (basic pH) do not emit fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…In the case that this second molecule emits light, then the phenomenon is called FRET. According to Ji and coworkers, in dendrimers this mechanism occurs between the ammonium ion from a tertiary amine and the amide ion from the tautomeric equilibrium [9c] . At pH 7 and lower, all the tertiary amines are fully protonated, so it facilitates the occurrence of the FRET mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…For example, two relatively strong but comparable fluorophore centers, (i.e., corresponding to fluorescence decay curve components 2 and 3 in this study) are distinctly noted in this analysis [ 28 ]. It has previously been demonstrated that the brightest fluorophore (component 3, in our tecto(dendrimers) contributing half of total fluorescence output) is derived from interactions of tertiary amino groups and imidic acid moieties along the terminal PAMAM branches and that its brightness and quantum yield are enhanced by branch stabilization [ 54 , 55 , 56 ]. In the case of tecto(dendrimers), this stabilization is probably conferred both by the 4-CMP modification as well as by the enhanced rigidity of the core-shell tecto(dendrimer) architecture.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the fluorescence was directly related to the dendrimers’ common tertiary amine and/or amide backbones. Recent studies by Qian et al suggest that the imine bond in the imidic acid group present within the PAMAM structure is responsible for emission [ 39 , 40 ]. In our studies, we propose that aerobic oxidation of the imine may be responsible for the fluorescence observed from the Schiff-base crosslinked hydrogels.…”
Section: Introductionmentioning
confidence: 99%